Hubungan Program Pendidikan Dan Pelatihan Dengan Kinerja Karyawan Administrasi Pada Universitas Tribhuwana Tunggadewi Malang - Gunawan Eko Nurtjahjono, (Bisnis dan Manajemen, 2010)
This Paper tries to describe and to analize a correlation education and training with employee performance, Meanwhile, the method of analysis used descriptive quantitative with sample as twenty four employee. The result show that there is a significant correlation between education and training with employee performance (r count 0,760 > r table 0,404, if r count is greater than r table, there is a significant and positive between two variables). It is suggested that the institution must develop their employees through human resource development program.